TINGKAT KEPARAHAN KARIES GIGI PADA MASYARAKAT SUKU BADUY MENGGUNAKAN INDEKS PUFA - Ulliana, Ulliana; Sulistiani , Silvia (Poltekkes Kemenkes Bandung, 2025)
Dental health is essential to help with speech, eating, and social interaction. The problem of cavities remains a common health issue, including in the Banten Province area. The Baduy indigenous community that holds fast to tradition tends to reject the influence of modernization, especially related to health. Caries that are not treated can continue to become a disease of the tooth pulp, so it is necessary to assess the severity using the PUFA index. The goal is to find out the severity of dental caries and the factors that affect the severity of dental caries in the Baduy people. The data collection approach uses survey methods. Respondents to community service as many as 50 respondents were identified risk factors for dental caries and the severity of dental caries. The results showed that there was no significant relationship between age (p-value 0.168) and sex (OR = 0.732, p-value 0.836) and the severity of dental caries, but there was a significant relationship between dental and oral maintenance habits and caries severity (p-value 0.000). Community service was found to be a significant relationship between dental care habits and caries severity.